Internet connectivity disruption in Russia (Russia) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity mixed detected in Russia. Data sourced from IODA, CensoredPlanet.
Censorship Incident ID: RU-2026-0148. Severity: critical. Confidence: 67%